Book review: Heather Montgomery and Mary Kellett (Eds.) (2009). Children and young people's worlds. Developing frameworks for integrated practice. Bristol, The Policy Press, 261pp, ISBN 978-1-84742-387-0 - Peter Evans (Scottish Journal of Residential Child Care)
Children and young people's worlds: developing frameworks for integrated practice is primarily a course text, edited by Heather Montgomery and Mary Kellett, for students on the Open University Childhood and Youth Studies postgraduate degree. Nevertheless, the book raises questions and promotes thought on what exactly it means to be a child in the 21st century, making it relevant to all professions working with children, including those practicing in residential childcare. Drawing its focus from the children's rights perspective, the book comprises fourteen chapters, written by eleven authors, considering this issue from a national and an international perspective.